Identification of the toxin components of Rhizoctonia solani AG1-IA and its destructive effect on plant cell membrane structure - Xu, Shanshan; Ren, Shaofeng; Bao, Wenjing; Li, Xiaoguang; Zhang, Yumei; Yu, Buzhu; Li, Weiqi; Li, Chengyun; Dong, Wenhan; Yang, Genhua (Frontiers in Plant Science, 2024)
Rice sheath blight is a fungal disease caused mainly by Rhizoctonia solani AG1-IA.Toxins are a major pathogenic factor of R. solani, and some studies have reported their toxin components; however, there has no unified conclusion. In this study, we reported the toxin components and their targets that play a role in R. solani AG1-IA. First, toxins produced by R. solani AG1-IA were examined. Several important phytotoxins, including benzoic acid (BZA), 5-hydroxymethyl-2-furanic aid (HFA), and catechol (CAT), were identified by comparative analysis of secondary metabolites from AG1-IA, AG1-IB, and healthy rice. Follow-up studies have shown that the toxin components of this fungus can rapidly disintegrate the biofilm structure while maintaining the content of host plant membrane components, thereby affecting the organelles, which may also explain the lack of varieties highly resistant to sheath blight.